2015
DOI: 10.12816/0026421
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Work Ethics ( IWE ) : A Review of Litrature and Directions for Future Research

Abstract: This paper summarizes and reviews the existing literature on Islamic Work Ethics (IWE) based on 28 empirical papers published in various journals in the last three decades. A multilevel integrated framework of IWE based on existing literature has also been proposed which represents all the citied studies in a single framework. The issues in previous research along with knowledge gaps in IWE related literature have also been identified. Keeping in view the significance of IWE in Muslim societies and the need fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 38 publications
(65 reference statements)
2
29
0
Order By: Relevance
“…Another significant extension to the LMX comes from confirmation of the moderating role of IWE in development of OI. Results suggested that increased level of relationship with leader combined with IWE strength might be more useful (Khan, Shahzad, & Usman, 2015). The theoretical boundary of the LMX is further extended to relationship oriented contexts of organizations practicing IWE to predict OI and citizenship behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Another significant extension to the LMX comes from confirmation of the moderating role of IWE in development of OI. Results suggested that increased level of relationship with leader combined with IWE strength might be more useful (Khan, Shahzad, & Usman, 2015). The theoretical boundary of the LMX is further extended to relationship oriented contexts of organizations practicing IWE to predict OI and citizenship behavior.…”
Section: Discussionmentioning
confidence: 99%
“…There are several definitions for job satisfaction. For example, Fisher and Hanna defined job satisfaction as an internal factor that is a kind of emotional adaptation to occupation and employment conditions [11]. Locke defined job satisfaction as a pleasant or positive emotional state that comes from evaluating one's job or job experience [12].…”
Section: Introductionmentioning
confidence: 99%
“…Second, we answer recent calls for more research exploring potential mediators, based on theoretical explanations, between employees' IWE and their positive behaviors (Usman et al 2015) and propose a new perspective based on social identity theory (Tajfel 1974) and self-consistency theory (Korman 1970). Thus, we explore the mediating effects of employees' moral identity in the relationships between their IWE and their promotive and prohibitive voice behaviors.…”
Section: Introductionmentioning
confidence: 87%
“…While the first empirical study on IWE (Ali 1988) was published more than two decades ago, studies on the implications of IWE for workplace attitudes and behaviors are very limited. In reviewing the 28 studies on IWE published in the last two decades, Usman et al 2015 Second, prior IWE research mostly fails to explore the underlying mediating mechanisms or well-acknowledged theory(ies) from psychology and organizational behavior literature to explain how the IWE influences work attitudes and behaviors (Usman et al 2015).…”
Section: Islamic Work Ethic (Iwe)mentioning
confidence: 99%